Moral sensitivity of primary care professionals in situations of vulnerabilities related to suicidal behavior (Research, Society and Development, 2021)
Objective: To analyze the performance of primary health care professionals on suicidal behavior from the conceptual perspective of vulnerability and moral sensitivity in a municipality of Santa Catarina. Method: Qualitative study through semi-structured interviews with 19 primary health care professionals. The data were analyzed based on content analysis. Results: From the perception of professionals, it was possible to identify an expanded view regarding the multicausality/manifestations of suicidal behavior, it was also possible to point out that the professional approach added to the response of institutions and co-participation of family/society can generate, perpetuate and transform vulnerabilities, and finally, there was insufficient health actions, representing opposition to the objective of overcoming vulnerabilities. Conclusion: In moral sensitivity, perceiving the problem must be tied to rethinking practice. Innovation of actions and search for resources that permeate barriers go towards the defense of the rights of the person in suffering, disruption of vulnerabilities and alleviation of professional suffering. The differential of the problem of suicidal behavior lies in understanding from the perspective of vulnerability and moral sensitivity, which allowed us to point out the continuous need to improve skills that impact intervention strategies, as well as to direct the gaze to the worker who begins to deal with anguish triggered from ethical problems.